REFORMASI EKONOMI HABIBIE 1998-1999: SEBUAH KEBIJAKAN ATASI KRISIS EKONOMI ORDE BARU - Afiyah, Mahilda Saidatul (Universitas Negeri Malang, 2021)
Indonesia's economy experienced a monetary crisis during the leadership of President Suharto where from 1997-1998 there were various economic problems that ended with the decline of President Suharto's power. Leadership turned to the hands of B.J Habibie who tried hard to restore the condition of the national economy through his economic policies. President B.J Habibie focused his economic policy on strengthening and recovering the economy after the monetary crisis. Ada improvement in terms of the economy that experienced inflansi and decreased exchange rate or rupiah exchange rate against the US dollar. On the other hand, there is a decrease in people's purchasing power as well as a lack of public trust in the president who is considered part of the New Order.Perekonomian Indonesia mengalami krisis moneter pada era kepemimpinan Presiden Soeharto dimana dari tahun 1997-1998 terjadi berbagai permasalahan ekonomi yang berakhir dengan penurunan kekuasaan Presiden Soeharto. Kepemimpinan beralih ke tangan B.J Habibie yang mana berusaha keras untuk mengembalikan kondisi perekonomian nasional lewat kebijakan ekonominya. Presiden B.J Habibie memfokuskan kebijakan ekonominya pada penguatan serta pemulihan ekonomi pasca krisis moneter yang terjadi. Ada perbaikan dari segi perekonomian yang mengalami inflansi serta penurunan nilai tukar atau kurs rupiah atas dollar AS. Di sisi lain, ada penurunan daya beli masyarakat serta kurangnya kepercayaan masyarakat terhadap presiden yang dianggap sebagai bagian dari Orde Baru.